A multi country comparison of the tuberculosis and endocrine related mortality in public health perspective (Annals of Medical Research, 2023)
Aim: The aim of the study is to examine tuberculosis and endocrine-related deaths worldwide from WHO ICD-10 data with multi-country comparisons.Materials and Methods: ICD-10 mortality data of WHO was used. Given mortality codes were examined, and mortality data records for 14 countries between 1996 and 2017 were used.Results: For people over 60 ages, the most common mortality was reported for endocrine, nutritional and metabolic diseases, followed by respiratory related deaths. Respiratory related mortality is the most dominant mortality among other tuberculosis mortality and endocrine, nutrition and metabolic diseases related mortality. The most frequent mortality was reported in 2005, followed by 2004 and 2003. Infant deaths and 60 and above age mortality differences between gender groups were statistically insignificant for all mortality causes of the research (p>0.05). For under 60 ages, respiratory and other tuberculosis related mortalities were significantly higher in the male patients (p
Keywords: Tuberculosis; Endocrine; Mortality; ICD-10